Exploring the nonlinear relationship between serum uric acid to high-density lipoprotein cholesterol ratio and obesity in older adults: a cross-sectional study - Fanchang Wang; Hongyang Qiao; Yi Zheng; Yating Zheng; Yuxin Ni; Xiaoming He (Frontiers in Public Health)
BackgroundThe prevalence of obesity, a common metabolic disorder, has been increasing annually, particularly in older adults. This trend poses a significant socioeconomic burden. The uric acid to high-density lipoprotein cholesterol ratio (UHR) was defined by dividing UA (mg/dL) by HDL-C (mg/dL) and multiplying by 100%. According to recent clinical research, UHR has emerged as a potential innovative indicator in metabolic status evaluation, supported by contemporary biomarker research. This cross-sectional study investigated the association between the UHR index and obesity prevalence among older Americans.ObjectiveThis cross-sectional research employed nationally representative survey data to Examine the connection between the UHR index and obesity among older individuals aged 60 and above.MethodsThis study utilized data from the National Health and Nutrition Examination Survey (NHANES) spanning 2011 to 2016. Individuals who were 60 years old or older were included in the study (n = 3,822). The relationship between UHR levels and obesity (as measured by a body mass index of 30 kg/m2 or greater or a waist-to-height ratio (WHtR) ≥0.5) was investigated using weighted multivariable logistic regression analyses, with adjustments made for sociodemographic characteristics, behavioral patterns, and clinical covariates, adjusting for sociodemographic, behavioral, and clinical covariates. Restricted cubic spline, ROC curves, threshold analysis, and subgroup analysis were also used.ResultAfter full adjustment for confounders, UHR was positively associated with the risk of obesity as defined by BMI (highest quartile vs. lowest quartile: OR = 6.13, 95% CI = 4.01–9.39; P-trend < 0.001) and UHR was positively associated with the risk of obesity as defined by WHtR (highest quartile vs. lowest quartile: OR = 20.21, 95% CI = 8.33–49.02; p-trend < 0.001). In addition, The restricted cubic spline analysis uncovered a nonlinear dose-response relationship (P < 0.01), and threshold analysis found inflection points of −2.485 in obesity defined by BMI and −2.503 in WHtR. Subgroup analyses showed that the association between UHR and obesity in older Americans was consistent across subgroups, demonstrating high reliability (all P-interaction > 0.05). The AUC for UHR predicting obesity defined by BMI was calculated to be 0.65 (95% CI = 0.63–0.66). The UHR predicted AUC for obesity as defined by men's body mass index (BMI) was 0.67 (95% CI = 0.65–0.70). UHR predicted an AUC of 0.69 (95% CI = 0.67–0.72) for obesity defined by body mass index (BMI) in females. The AUC for UHR predicting obesity defined by WHtR was calculated to be 0.75 (95% CI = 0.72–0.78). UHR predicted an AUC of 0.76 (95% CI = 0.72–0.80) for obesity defined by WHtR in males, and UHR predicted an AUC of 0.83 (95% CI = 0.79–0.87) for obesity defined by WHtR in females.ConclusionThe findings demonstrate a notable positive correlation between UHR and obesity in older adults, with this association remaining evident following adjustment for multiple confounding variables. These results imply that systematic evaluation of UHR levels could serve as an effective strategy for proactively detecting populations susceptible to obesity-related metabolic disorders.